Influence of carbon chain length on physical properties of 3FmHPhF homologues. Issue 15 (8th December 2019) - Deptuch, A.; Marzec, M.; Jaworska-Gołąb, T.; Dziurka, M.; Hooper, J.; Srebro-Hooper, M.; Fryń, P.; Fitas, J.; Urbańska, M.; Tykarska, M.
ABSTRACT: Four compounds from 3FmHPhF homologous series of chiral smectogenic fluorinated compounds (m = 2, 4, 5, 6) were studied by frequency domain dielectric spectroscopy, electro-optic measurements, X-ray diffraction and differential scanning calorimetry. Values of the relaxation time and dielectric increment of relaxation processes versus temperature and bias field were determined. The temperature-dependent tilt angles, spontaneous polarisations, switching times, rotational viscosities, and average intermolecular distances and correlation lengths within smectic layers were obtained. Experimental results were supplemented by density functional theory calculations of isolated 3FmHPhF molecular geometries, and the relationship between the molecular structures and the transverse component of their dipole moments was studied for the mesogens with m = 2, 4, 5, 6, 7. The results are discussed in terms of the length of the Cm H2m flexible carbon chain of the homologues. Graphical abstract: